Synthesis of the Algorithm of the Vector Width-Pulse Modulation in a Nine-Phase Active Voltage Rectifier - S. V. Panteleev; A. N. Malashin; D. V. Karkotskiy; Yu. V. Suchodolov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
The article is devoted to the problems of synthesis of multiphase electromechanic modules consisting of a multiphase electrical machine (m > 3) and a multiphase controlled converter. In the multi-phase design of the electric machine, it is possible to obtain a trapezoidal electromotive force and to increase the specific power conversion provided that the EMF and the current at the output of the m-phase generator are matched. The development of the vector pulse width modulation algorithm for the m-phase active voltage rectifier is considered, which will make it possible to match the shape and phase of the currents and voltages at the output of the m-phase generator in order to obtain the maximum active power of the module under study. The analysis of possible combinations of states of the keys of a nine-phase active rectifier is carried out. Each key state is assigned a base vector in a fixed coordinate system. It is noted that there are a number of combinations in which two or more different key states correspond to one base vector. The system of basic vectors is differentiated into its constituent levels, sectors and subsectors. In order to obtain any given voltage vector that does not coincide with the base vectors, the method of spacevector modulation is used. This method provides using 100 % DC link voltage as compared with sinusoidal pulse width modulation (86.6 %). The goal of space-vector modulation for a nine-phase active voltage rectifier is to implement the resultant spatial vector of the output voltage with a given average value within the modulation period. For this, the three vectors nearest to the given base vector must be found. To implement a given voltage vector, a sequence of sampling the base vectors in the modulation period is given, providing one commutation (commutation of two complementary keys) while passing from one basic vector to another to reduce switching losses. Analytic relationships of the weight coefficients for the generators of vectors are obtained, as well as the equations of the boundaries of the subsectors that form a diagram of combinations of states of the circuit. The sequence of the calculations presented in the paper is a technique for realizing the vector pulse-width modulation in nine-phase controlled electrical energy converters.